Is wage labor in highly developed capitalism today still a force of social transformation? - Martin Kronauer (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2018)
The article deals with the question why in many European countries as well as in the USA significant parts of the working classes today support nationalistic and xenophobic political parties and movements. It reviews two different answers which are currently hotly debated in the political left. One answer refers to an imperial mode of living in highly developed capitalist countries which cuts across class divisions and also includes the working classes. The argument holds that the latter, too, defend their (relative) privileges based on the social and ecological exploitation of the global South. Another answer points to the political and symbolic marginalization of the working classes due to the reign of neoliberalism and the failure of the left to fight it. The turn to the right seems in this light to be a misguided response to the effects of neoliberal globalization on the working-class conditions and the lack of a credible left alternative. The article discusses merits and shortcomings of both answers. It then takes another approach to the issue of the marginalization of the working class, suggests to enlarge the social and political perspective to include a much broader variety of wage labor, and to address their common grievances in order to form new alliances for social transformation. Struggling for a more egalitarian society, the article holds, would also be a necessary step to address the pressing issues of global social exploitation and ecological devastation.
Keywords: 330; working class; right-wing tendencies; social transformation; wage-labor alliance